Tax of industry and Trade in the last decade of Tocancipa's municipality (2015)
The present work is show the importance of the tax of industry and Tocancipá trade, which is one of the most important factors for the financing of the municipality; on the other hand hara a study where it appears since has developed throughout a decade.